Sistem Informasi Surat Elektronik Badan Diklat Keagamaan Kota Medan Berbasis Web Menggunakan Penegembangan Waterfall - Adelia Fairiza Putri; Cindy Aulia Amanda; Zidanul Akbar; Ziyad Habibul Mikraj (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Work Practice is a form of providing education and skills training that systematically and synchronously combines educational programs on campus and skills mastery programs obtained through working in the world of work, aimed at achieving a certain level of professional expertise. This work practice is part of an internship program implemented by the North Sumatra State Islamic University (UINSU) consisting of students from the Computer Science Study Program, Faculty of Science and Technology. North Sumatra State Islamic University (UINSU). The author was assigned to the Medan City Religious Education and Training Agency, one of whose duties was compiling and archiving documents. The author supervises and reviews the progress of structuring and writing documents at the Education and Training Agency. The method for implementing the internship/field work practice program (Magang) used by students is Project Based Learning (PBL) is a teaching method where students learn by being actively involved in projects in the real world and with personal meaning. This MBKM program internship activity results in the transfer of knowledge, transfer of skills, and transfer of new technology which will be useful for students as guidance and useful experience in the world of work in the future.